Elevated IL-6 plasma levels are associated with GAD antibodies-associated autoimmune epilepsy - Basnyat, Pabitra; Peltola, Maria; Raitanen, Jani; Liimatainen, Suvi; Rainesalo, Sirpa; Pesu, Marko; Peltola, Jukka (Frontiers in Cellular Neuroscience, 2023)
Background: Antibodies against glutamic acid decarboxylase (GADA) are present in multiple neurological manifestations, such as stiﬀ-person syndrome, cerebellar ataxia, limbic encephalitis, and epilepsy. Increasing data support the clinical significance of GADA as an autoimmune aetiology of epilepsy; however, there is not yet definitive evidence to confirm the pathogenic link between GADA and epilepsy. Objective: Interleukin-6 (IL-6), a pro-convulsive and neurotoxic cytokine, and interleukin-10 (IL-10), an anti-inflammatory and neuroprotective cytokine, are crucial inflammatory mediators in the brain. Increased production of IL-6 and its association with epileptic disease profiles are well established, suggesting the presence of chronic systemic inflammation in epilepsy. Therefore, in this study, we investigated the association of plasma cytokine concentrations of IL-6 and IL-10 and their ratio with GADA in patients with drug-resistant epilepsy. Methods: IL-6 and IL-10 concentrations were measured by ELISA in plasma, and the IL-6/IL-10 ratio was calculated in a cross-sectional cohort of 247 patients with epilepsy who had their GADA titers measured previously for their clinical significance in epilepsy. Based on GADA titers, patients were grouped as GADA negative (n=238), GADA low positive (antibody titers <1000 RU/mL, n=5), and GADA high positive (antibody titers ≥1000 RU/mL, n=4). Results: Median IL-6 concentrations were significantly higher in patients with high GADA positivity (2.86 pg/mL, interquartile range [IQR] = 1.90–5.34 pg/mL) than in GADA-negative patients (1.18 pg/mL, interquartile range [IQR] = 0.54–2.32 pg/mL; p = 0.039). Similarly, IL-10 concentrations were also higher in GADA high-positive patients (1.45 pg/mL, interquartile range [IQR] = 0.53–14.32 pg/mL) than in GADA-negative patients (0.50 pg/mL, interquartile range [IQR] = 0.24–1.00 pg/mL); however, the difference was not statistically significant (p = 0.110). Neither IL-6 nor IL-10 concentrations were different between GADA-negative and GADA low-positive patients (p>0.05) or between GADA low-positive or GADA high-positive patients (p>0.05). The IL-6/IL-10 ratio was also similar among all the study groups. Conclusion: Increased circulatory concentrations of IL-6 are associated with high GADA titers in patients with epilepsy. These data provide additional pathophysiological significance of IL-6 and help to further describe the immune mechanisms involved in the pathogenesis of GADA-associated autoimmune epilepsy.